2016
DOI: 10.1080/00016489.2016.1225316
|View full text |Cite
|
Sign up to set email alerts
|

Is the Keros classification alone enough to identify patients with the ‘dangerous ethmoid’? An anatomical study

Abstract: Keros type I, II, and III was noted in 9.2%, 75.8%, and 15.0% of cases, respectively. Despite some statistically significant correlations, it was not possible to identify the patient age, sex, and side of body clearly correlating with the critical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 18 publications
5
26
1
Order By: Relevance
“…Similar findings to Keros's study have been reported in in various countries such as South Korea [15], Turkey [18], Turkey [19], Turkey [20], Turkey [21], Turkey [22] , Thailand [23], Brazil [10], Germany [24], Egypt [25], Pakistan [26], Poland [27], Saudi Arabia [28], India [29], India [30] , and Iran [31]. Unlike to Keros study [9], and similar studies [10,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31] our findings showed that Type I is the most common type (71.0%), followed by Type II (27.4%) and the Type III (1.6%) of the cases, respectively. However, our findings inline to results reported in studies from Philippine [16], USA [32], UK [33], Nepal [34], Malaysia [35], and Egypt [36] which confirms that the Keros type I is the most common.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings to Keros's study have been reported in in various countries such as South Korea [15], Turkey [18], Turkey [19], Turkey [20], Turkey [21], Turkey [22] , Thailand [23], Brazil [10], Germany [24], Egypt [25], Pakistan [26], Poland [27], Saudi Arabia [28], India [29], India [30] , and Iran [31]. Unlike to Keros study [9], and similar studies [10,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31] our findings showed that Type I is the most common type (71.0%), followed by Type II (27.4%) and the Type III (1.6%) of the cases, respectively. However, our findings inline to results reported in studies from Philippine [16], USA [32], UK [33], Nepal [34], Malaysia [35], and Egypt [36] which confirms that the Keros type I is the most common.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise to several studies conducted in Turkey [19, [22], Poland [27], and Iran [31], our study found no statistically significant difference between males and females in all Keros types on both sides. In contrast, other studies from Philippine [16], Malaysia [35] and India [30] found a statistically significant difference in Keros types II between males and females and some other studies from Egypt [25], Saudi Arabia [28], and Pakistan [26] found a statistically significant difference between males and females in Keros type I.…”
Section: Discussionsupporting
confidence: 81%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ and left side contributes to the asymmetry in the ER configuration. In a radiological study by Skorek et al 12 , they found that Keros classification alone is not enough to identify the high-risk area at the skull base and the "dangerous ethmoids' . They recommended a classification that is based on the distance of olfactory fossa to both medial wall of orbit and the medial wall of middle turbinate as most ESS dissection occurs lateral to the middle turbinate.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggested that the risk of iatrogenic LLCP injury increases with the olfactory cleft depth (6)(7) . For this reason, the classification proposed in 1962 by Keros (8) is still the most commonly used today to estimate the risk of iatrogenic CSF-L.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Keros type 3 are supposed to have a greater risk of intracranial entry since the more pronounced depth of the cribriform cleft and the thinness of its bony wall make this area more susceptible to iatrogenic injuries (2,7) . Even though widely used, several authors highlighted the limitations of this classification system in fully describing the shape of the skull base and predicting the intracranial entry risk (6,(9)(10)(11)(12)(13) . Recently, our group proposed a new classification system of the anterior skull base anatomy based on the angle formed between the LLCP and the lateral extension of an horizontal plane passing through the cribriform plate (Gera classification).…”
Section: Introductionmentioning
confidence: 99%